ARCHITECTURAL BUILDINGS (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This article examines written and material sources documenting the formation and historical development of the architectural heritage of Nurata, one of the oldest historical and cultural centers of Central Asia.
Keywords: Nurata, architectural heritage, written sources, material sources, Bukhara Khanate, Central Asian architecture, source studies, cultural heritage.